(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article, the prolapse of genital organs in women, their occurrence rate, the course of pregnancy and the principles of carrying out pregnancy are studied and analyzed. There were 67 patients with genital prolapse in our women under observation, their average age was 29 to 40 years. Our patients were subjected to clinical laboratory tests and analysis, in addition, the severity levels of genital prolapse and observed complications were analyzed.